Zoonotic diseases and their drivers in Africa - Grace, Delia; Bett, Bernard K. (CAB International, 2014)
This chapter focuses on the link between livestock and zoonoses in sub-Saharan Africa. The role of poverty, keeping livestock beside or inside houses, low level of agricultural intensification and input use, and eating bushmeat in the emergence and persistence of zoonoses is described. The exceptional vulnerability to a deadly trifecta of climate change, high rates of demographic increase and uncontrolled disease is discussed.